The issue of recognition of ecocide as a crime by environmental courts and tribunals - Tulibayev, S.T. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article analyzes the recognition of ecocide as a crime by judicial institutions. Ecocide still has not received a well recognized definition. However, the proposal to acknowledge ecocide as an international crime developed by the Independent Expert Panel for the Legal Definition of Ecocide, as well as the recognition of environmental crimes similar to ecocide as set out in the Proposal for a Directive of the European Parliament and of the Council on the protection of the environment through criminal law, should be highlighted and analyzed. The purpose of the study is to analyze the impact of new approaches to the crime of ecocide on the practice of environmental courts and tribunals. By the application of general and specialized research methods, the author identifies possible changes in the jurisprudence of already existing judicial institutions, as well as the likelihood of the emergence of international courts and tribunals dedicated to separate cases of ecocide. The article concludes that new approaches to the definition of ecocide may lead to further development of international environmental law and national environmental law of the Republic of Kazakhstan, as well as the possible emergence of effective international mechanisms to protect international environmental security.
Экологиялық соттар және трибуналдарының экоцидті қылмыс деп тану мәселесі
Проблема признания экоцида преступлением экологическими судами и трибуналами
Keywords: ecocide; environmental law; environmental issues; international criminal law; national legislation; environmental court; environmental tribunal; environmental security; International Criminal Court; Independent Expert Panel for the Legal Definition of Ecocide